Faktor Risiko Low Back Pain pada Pekerja Pemetik Teh di Perkebunan Teh Ciater Kabupaten Subang - Syuhada, Ambar Dani; Suwondo, Ari; Setyaningsih, Yuliani (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2018)
Background: Low back pain, pain that is felt in the affected anatomical area with a variety of long occurrence of pain. This pain feels lumbar or lumbo-sacral. Tea pickers are at risk of low back pain due to their activities such as the position of bending, lifting and carrying heavy loads. This research aim to factors that risk against the incident of low back pain.Method: Total sample of 132 respondents: 66 cases and 66 controls were selected randomly from the tea pickers workers. Data analysis using Chi Square and logistic regression to know the mostdominant factor.Results: There was relationship of employment, back posture, heavy weights with low back pain (P <0.05). There was not relationship age, sex, smoking, body mass index and physical activity with low back pain (p>0.05). Multivariate analysis using logistic regression showed the most dominant working period affecting low back pain. The study found that low back pain was a relevant health problem among tea picker workers. The policy of arranging breaks and lifting techniques is required to prevent low back pain.Keywords: Low back pain, risk factors, the tea pickers